Seasonal variation in mortality rates for Whimbrels (Numenius phaeopus) using the Western Atlantic Flyway. (5th February 2019) - Watts, Bryan D; Smith, Fletcher M; Hamilton, Diana J; Keyes, Tim; Paquet, Julie; Pirie-Dominix, Lisa; Rausch, Jennie; Truitt, Barry; Winn, Brad; Woodard, Paul
Abstract: For most shorebird species, our understanding of the basic limiting factors and when or where they operate during the annual cycle is currently inadequate to either understand ongoing declines or effectively allocate conservation resources for recovery. Whimbrels ( Numenius phaeopus ) exhibit delayed recruitment and have low fecundity, and populations with such life-history traits are often vulnerable to increases in adult mortality. We tracked 33 adult Whimbrels with satellite transmitters for 12, 802 bird-days to investigate patterns in survival and recorded 16 probable and 5 confirmed mortalities. We used Cox's proportional hazards model to estimate daily hazard rates by season and a Kaplan-Meier product limit estimator to estimate monthly survival. Daily hazard rates varied by season and were 5 times higher during migratory periods (fall and spring migration) compared to stationary periods (winter and breeding). Estimated annualized survivorship was 0.54 ± 0.21 (SE) and on the lower end of the range of 0.8–0.9 believed to be required to maintain a stable population. More than half of the mortality recorded during the study occurred during the fall hunting season and within the last remaining area throughout the Western Hemisphere where significant legal and illegal hunting occurs. One-third of mortality occurred during spring migration either within terminal staging sites or as birds made final movements to breeding grounds. Survival during the migratory periods may have been influenced by the use of transmitters.